Study of prevalence and etiological factors in relation with recurrent admissions of patients in Psychiatric department at Hospital Tengku Ampuan Afzan, Kuantan,Pahang, Malaysia - Ali, Syed Masroor; Musa, Ramli; Al-Ani, Ali Sabri Radeef; Abu Bakar, Ahmad Zafri (2013)
Background & Aims: With reduction in number of patients in the Psychiatric hospitals in Malaysia, the Psychiatric department of general hospitals became overloaded. High readmission rate has been often measured as poor prognostic out comes. A huge amount of budget consumed on patients admissions and the readmission rate is considered as a performance indicator. Therefore, the aim of this study is to find out the social, demographic, and clinical profile of frequently re-hospitalized psychiatric patients. Methods: cross sectional study, sample size 250 patients, 6 months duration. • Consent obtained. •Inclusion criteria: 1. Age: 18 years and above. 2. Participants: diagnosed and admitted by psychiatrist. 3. Conversant in Malay or English. • To interview, using questionnaires about mental illness, precipitating factors, high expressed emotion, and psychiatric services. Results: In 5 months admitted patients 172 (Males: 92, Females: 80). 132 (76.7%) were re admitted. GENDER: A. Males: 74 (55.3%) B. Females: 58 (44.7%) DIAGNOSIS: Schizophrenia: 101 Bipolar : 6 MDD : 5 Substance abuse: 13 MR : 7 REASONS: Poor compliance : 89 Family rejection : 9 Discharge without full remission: 10 Others : 24 Conclusion: Ongoing unfinished study but trend has shown that majority of patients are readmitted and the leading cause is poor compliance in schizophrenics.